Understanding attitudes toward artificial intelligence: the role of self-efficacy and social presence - Loureiro, S. M. C.; Rodrigues, M. B.; Gonçalves, D.; Bilro, R.G. (2025 Global Marketing Conference at Hong-Kong Proceedings, 2025)
The rapid advancement of Artificial Intelligence (AI) has revolutionized various industries by enhancing efficiency, streamlining processes, and transforming service delivery. While the integration of AI in sectors like healthcare, logistics, and tourism has been widely studied, its adoption within the corporate events industry remains underexplored. Existing research on AI acceptance often relies on traditional technology acceptance models (e.g., TAM), which were developed for non-intelligent systems and may not fully capture the socio-psychological nuances influencing users’ attitudes toward AI systems. This study addresses this gap by investigating how socio-psychological factors – social presence, technological self-efficacy and perceived empathy – shape delegates’ attitudes toward AI acceptance in the context of corporate events. Grounded in a user-centric perspective, this research examines whether these factors influence participants’ intentions and attitudes toward adopting AI-driven systems during service delivery. Beyond providing insights into AI’s role in the corporate events sector, this paper contributes to the broader understanding of human-AI interaction by exploring the psychological and social dimensions that drive acceptance. By empirically validating the significance of these factors, this study highlights the potential of AI integration as a strategic tool for enhancing attendee experiences and fostering innovation in modern business event management.